PENGARUH PELATIHAN KETERAMPILAN DAN PENGEMBANGAN KARIR TERHADAP PERSIAPAN KARIR DENGAN KUALITAS KEHIDUPAN KERJA SEBAGAI VARIABEL MODERATING STUDI PADA MAHASISWA FAKULTAS FEB UNIVERSITAS MUHAMMADIYAH SURAKARTA - Rini Maharani; Irmawati (JURNAL ILMIAH EDUNOMIKA, 2026)
Changes and competition in the world of work require students to be well prepared for their careers from an early age. Career preparation is influenced by involvement in skills training and a continuous career development process. In addition, the quality of working life is seen as a supporting condition that can strengthen or weaken students' career readiness in facing the world of work.This study aims to analyse the correlation between career training and career development on career preparation, using quality of work life as a moderating variable among students of the Faculty of Economics and Business, Muhammadiyah University Surakarta. The methodology applied is a quantitative approach through the distribution of questionnaires to 109 student respondents. The sampling technique used probability sampling with purposive sampling. Data analysis was conducted using Partial Least Squares Structural Equation Modelling (PLS-SEM) with the support of SmartPLS software. The research findings reveal that skills training has a significant effect on career preparation, career development has a positive impact on career preparation, quality of work life has a positive effect on career preparation, quality of work life does not mediate skills training on career preparation, and quality of work life mediates career development on career preparation.